Combining Zinc Phthalocyanines, Oligo(p-Phenylenevinylenes), and Fullerenes to Impact Reorganization Energies and Attenuation Factors - Krug, Marcel; Stangel, Christina; Zieleniewska, Anna; Clark, Timothy; Torres, Tomas; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (ChemPhysChem, 2019)
A study on electron transfer in three electron donoracceptor complexes is reported. These architectures consist of a zinc phthalocyanine (ZnPc) as the excitedstate electron donor and a fullerene (C-60) as the groundstate electron acceptor. These complexes are brought together by axial coordination at ZnPc. The key variable in our design is the length of the molecular spacer, namely, oligopphenylenevinylenes. The lack of appreciable groundstate interactions is in accordance with strong excitedstate interactions, as inferred from the quenching of ZnPc centered fluorescence and the presence of a shortlived fluorescence component. Fullfledged femtosecond and nanosecond transient absorption spectroscopy assays corroborated that the ZnPc C-+(60) chargeseparated state formation comes at the expense of excitedstate interactions following ZnPc photoexcitation. At a first glance, the ZnPc C-+(60) charge separated state lifetime increased from 0.4 to 86.6 ns as the electron donoracceptor separation increased from 8.8 to 29.1 angstrom. A closer look at the kinetics revealed that the changes in chargeseparated state lifetime are tied to a decrease in the electronic coupling element from 132 to 1.2 cm(1), an increase in the reorganization energy of charge transfer from 0.43 to 0.63 eV, and a large attenuation factor of 0.27 angstrom(1).
CRIS-Team WoS Importer:2019-11-08